On-Demand Release of Protective Agents Triggered by Environmental Stimuli - Giuliani, Chiara; Messina, Elena; Staccioli, Maria Paola; Pascucci, Marianna; Riccucci, Cristina; Liotta, Leonarda Francesca; Tortora, Luca; Ingo, Gabriel Maria; Di Carlo, Gabriella (Frontiers in Chemistry, 2020)
The aim of this study is to develop smart materials with stimuli responsive properties for the long-term protection of steel. The idea is to obtain a tailored and controlled release of protective agent in response to the environment stimuli. First, the protective efficacy of three inhibitors containing a carboxylic moiety, such as p-aminobenzoic (pAB), succinic (SA) and caffeic (CA) acids, was investigated in alkaline chloride solutions. The results reveal that pAB is the most effective protective agent, significantly better than SA and CA. It is surprising that steel surface in pAB solution remains unchanged even after 5 months of corrosion treatment, whereas the formation of degradation products in SA and CA solutions was observed after only 6 days. Based on these findings, pAB was selected and used for the functionalization of silica nanoparticles and layered double hydroxides (LDHs) that can act as delivery vehicles and inhibitor reservoir. Specifically, pAB was chemisorbed on silica amino groups via an amide bond and this makes possible a gradual inhibitor release induced by an alkaline environment. The intercalation of pAB in its anionic form into the LDHs structure is responsible for a completely different behavior, since the release is induced by chloride ions and occurs by an anionic exchange reaction. Thus, these materials play a dual role by acting as inhibitor reservoir and by capturing chlorides. These findings reveal that is possible to create a reservoir of corrosion inhibitor gradually released on demand based on the chemical environment. The stimuli responsive properties and the complementary protective action of inhibitor-loaded silica and LDHs make them attractive for a long-term protection of steel and open the way to innovative solutions for the preservation of concrete cultural heritage.